Crack Evolution Characteristics and Cracking Mechanism of Red Beds in Central Sichuan during Seepage and Swelling. (28th April 2021) - Zhou, Zhe; Chen, Shanxiong; Wang, Yinhui; Dai, Zhangjun
Abstract : Crack is one of the important factors affecting the engineering characteristics of expansive rock and soil. In order to study the evolution characteristics and cracking mechanism of red beds in Central Sichuan during seepage and swelling, multiple groups of cracking tests are conducted under different initial states with a self-made device. In addition, combining swelling-softening mechanism of expansive rock and numerical analysis, the swelling-cracking mechanism is studied. The following research results are obtained. (1) The evolution process of swelling cracks is divided into three stages: the generation stage, the rapid development stage, and the stabilization stage. In the rapid development stage, the increase in the crack degree accounts for 90% of the whole process. (2) The final crack degree of the sample is related to the initial water content, water absorption method, and clay mineral content. The lower the initial water content, the greater the final crack degree of the sample. The final crack degree under the soaking water absorption method is greater than that under the capillary water absorption method, and the final crack degree of mudstone is greater than that of argillaceous sandstone and sandstone. (3) The development of swelling cracks is controlled by three significant values of water absorption, which are w 1, w 2, and w 3, respectively, representing the beginning of cracking, the starting of the rapid development stage, and the starting of the stabilization stage. Among them, w 2 is of great significance in engineering practice. It shows that the development of cracks has entered a stage of rapid development, and the crack degree in this stage will increase exponentially with water absorption. (4) Uneven water absorption and uneven distribution of clay minerals lead to uneven swelling of expansive rock, which in turn generates swelling stress. Under the combined action of swelling stress and water swelling-softening, the internal structure of the rock is destroyed, leading to the generation and development of the cracks. Due to the different causes of uneven expansion, the mechanical mechanism of cracking and the shape of the resulting cracks will be different.